2004
DOI: 10.1007/s00011-004-1276-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of insulin-like growth factor-I in hyaluronan mediated repair of cultured cartilage explants

Abstract: The reparative effects of HA appear to involve enhanced PG synthesis through IGF-1 and requires cartilage matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
1
8
0
3
Order By: Relevance
“…A similar result was seen in cartilage explants, when exposure of free HA led to retention of IGF-1. 41 We speculate that, without HA in the alginate matrix, exogenous IGF-1 delivery suppresses IGF-1 expression, although as HA is introduced into the matrix, HA begins to sequester exogenous IGF-1, promoting endogenous IGF-1 expression. Finally, as higher amounts of HA are included within the alginate matrix, higher amounts of IGF-1 are retained, thus increasing chondrocyte exposure to IGF-1 and decreasing IGF-1 endogenous expression.…”
Section: Discussionmentioning
confidence: 98%
“…A similar result was seen in cartilage explants, when exposure of free HA led to retention of IGF-1. 41 We speculate that, without HA in the alginate matrix, exogenous IGF-1 delivery suppresses IGF-1 expression, although as HA is introduced into the matrix, HA begins to sequester exogenous IGF-1, promoting endogenous IGF-1 expression. Finally, as higher amounts of HA are included within the alginate matrix, higher amounts of IGF-1 are retained, thus increasing chondrocyte exposure to IGF-1 and decreasing IGF-1 endogenous expression.…”
Section: Discussionmentioning
confidence: 98%
“…Similar opposing effects of Hyalovet and HYAL-2 were observed in in vitro-produced sheep embryos (Marei et al 2016a). Small-sized HA has been shown to regulate the expression of IGFs (Homandberg et al 2004) and heat shock proteins (Xu et al 2002), which are important for early embryo development in the oviduct (Aviles et al 2010). We concluded that the presence of large-size HA in the vicinity of developing embryos disturbs the oviductal environment and embryo development.…”
Section: Pre-implantation Embryo Developmentmentioning
confidence: 84%
“…It was found that HA decreased release of IGF-I into the media and enhanced retention of fluorescently labeled IGF-I added to cartilage explants [56]. In order to implicate IGF-I further, the IGF-I blocker, rhIGF-I binding protein-2 was tested, which blocks access of IGF-I to its receptor, and found that it decreased the ability of HA to enhance PG synthesis and blocked the ability of HA to facilitate restoration of PG in Fn-f damaged cartilage [56]. Thus, HA compensated for Fn-f mediated damage through its ability to enhance PG synthesis through elevated activity of IGF-I.…”
Section: Introductionmentioning
confidence: 98%
“…IGF-I is the major PG synthesis promoting factor in cartilage and is known to be stored in the matrix [55]. It was found that HA decreased release of IGF-I into the media and enhanced retention of fluorescently labeled IGF-I added to cartilage explants [56]. In order to implicate IGF-I further, the IGF-I blocker, rhIGF-I binding protein-2 was tested, which blocks access of IGF-I to its receptor, and found that it decreased the ability of HA to enhance PG synthesis and blocked the ability of HA to facilitate restoration of PG in Fn-f damaged cartilage [56].…”
Section: Introductionmentioning
confidence: 98%